Comparison of the Effects of Media-based and Face-to-face Cardiac Rehabilitation Training Programs on Self-efficacy in Patients Undergoing Coronary Artery Bypass Grafting - Hamideh Mohebbi; Seyed Reza Mazlom; Mohammad Reza Kasraei; Zahra Hamedi; Hamidreza Hosseinikhah; Hossein Dehghan Moghimi; Fatemeh Ebrahimi; Javad Malekzadeh (Mashhad University of Medical Sciences, 2018)
Background: Several complications may occur in patients after coronary artery bypass grafting (CABG) leading to decreased self-efficacy. Rehabilitation training is the best method for reducing the complications and increasing self-efficacy. Various educational techniques lead to different rehabilitation results and levels of self-efficacy. Improving these measures requires the selection of the most appropriate educational technique. Aim: This study aimed to compare the effect of two media-based and face-to-face cardiac rehabilitation training methods on self-efficacy in patients undergoing CABG. Method: This clinical trial was conducted among 60 patients, who were randomly assigned into two groups, in Imam Reza Hospital, Mashhad, Iran, 2017. Cardiac rehabilitation training program was implemented face-to-face or using a researcher-made multimedia upon admission, discharge, at the start of cardiac rehabilitation, and at the end of the 10th session for half-hour. A researcher-constructed questionnaire on self-efficacy was completed by the participants in the mentioned stages. Data analysis was performed in SPSS software, version 16. Results: The mean ages of the participants in the face-to-face and multimedia groups were 56.0±8.1 and 57.5±7.3 years old, respectively. No significant difference was observed in the self-efficacy scores of the patients upon admission (P=0.36). However, there was a significant difference between the groups at the post-intervention stage (P